Analisis Faktor – Faktor Pendukung Pengambilan Keputusan Memilih Rumah Sakit Rujukan Di Bangka Belitung Dengan Analitycal Hierarchy Process - Hilyah Magdalena (Fountain of Informatics Journal, 2017)
Health services are basic services whose implementation is protected and guaranteed by the government. The existence of BPJS makes health services easier, more secure, and reachable to all levels of society. When a patient's health condition requires a higher facility, patients are generally referred to a higher-level health facility. In the province of Bangka Belitung currently stands several hospitals with various levels and completeness of facilities, ranging from provincial public hospitals, local public hospitals, to private hospitals. Patients who need referral can adjust the choice of the hospital with their health condition. The diverse needs of referral health care services and the diversity of hospitals with their services make decision making difficult. This study focuses on analyzing what factors are the basis of patient consideration in choosing a referral hospital. To support the multicriteria and multi-alternative selection process, this study uses the Analytical Hierarchy Process (AHP). The results of data processing showed that the most important criterion for patients when choosing a referral hospital was a health service attribute weighing 19.2% and the patients referred to were mostly referral patients in wards of wards with a weight of 24.2%.